Email
logo

Ask Questions, Get Answers

X
 
Answer
Comment
Share
Q)

The equation formed by decreasing each root of $ax^2+bx + c = 0$ by $1$ is $2x^2 + bx+ 2=0$, then :


( A ) $b=-c$
( B ) $c=-a$
( C ) $b=a+c$
( D ) $a=-b$

Please log in or register to answer this question.

Help Clay6 to be free
Clay6 needs your help to survive. We have roughly 7 lakh students visiting us monthly. We want to keep our services free and improve with prompt help and advanced solutions by adding more teachers and infrastructure.

A small donation from you will help us reach that goal faster. Talk to your parents, teachers and school and spread the word about clay6. You can pay online or send a cheque.

Thanks for your support.
Continue
Please choose your payment mode to continue
Home Ask Homework Questions
...